The global partnership against WMD success and shortcomings of G8 threat reduction since 9/11 - Heyes, Alan (Whitehall paper series, 2011)
The 9/11 terrorist attacks prompted a new urgency in efforts to deal with chemical, biological, radiological and nuclear proliferation. The potential acquisition and use by terrorist groups of such weaponry was suddenly a much increased threat. The G8 Global Partnership against the Spread of Weapons and Materials of Mass Destruction subsequently encouraged some twenty-two countries and the European Union to pledge up to $20 billion to address this challenge. The creation of the Global Partnership was the first time so many countries agreed to collaborate on a range of non-proliferation, security and nuclear safety programmes, as well as commit such an amount of resources to them. Based on extensive primary research, this Whitehall Paper assesses the success and shortcomings to date of the Global Partnership, and suggests how the mechanism can be bolstered and taken forward.